Novel solid state nitric oxide sensor using siloxane-poly (oxypropylene) (PPO) - Herculano, Rondinelli Donizetti [UNESP]; Brunello, Carlos Alberto; Melo Junior, Jair Pereira de; Martins, Mayler [UNESP]; Borges, Felipe Azevedo [UNESP]; Chiavacci, Leila [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP] (Scientific Research Publishing, 2013)
In this paper, a novel solid state Nitric Oxide (NO) sensor made of a spin trap (iron(II)-diethyldithiocarbamate complex, FeDETC) encapsulated in a siloxane-poly(oxypropylene) (PPO) matrix was developed. Nitric oxide (NO), a free radical molecule, has numerous roles in various physiological functions, such as the regulation of blood pressure, immune re- sponse to bacterial infection, and nervous systems. Siloxane-polyether hybrid materials, for example siloxane- poly(oxypropylene) (PPO), are easy to prepare, transparent and flexible. The combination of all these characteristics in a unique material allows it to be used in several scientific and technological areas, including human health. NO radical is trapped in FeDETC, which allows its detection by electron paramagnetic resonance (EPR). FeDETC was added while PPO was a sol, which was then left in air for gelation. The novel sensor was dived directly into a solution of NO, when the NO-FeDETC complex was formed. Our results show that the novel sensor responds to NO, with similar sensitivity as previously published sensors. PPO sensors present a strong EPR signal and a high stability, keeping its signal for 45 days. We have studied ways to accelerate the NO release from the sensor, in order to study its potential as a drug delivery system. We observed an acceleration in NO release by using a modulated magnetic field of 40 G at 100 kHz; as well as by UV irradiation. Thermal induced NO release was also tested by heating NO-FeDETC PPO up to 50°C, with good results.
Keywords: PPO; drug delivery; EPR